2016
DOI: 10.1038/srep22820
|View full text |Cite
|
Sign up to set email alerts
|

Heterogeneous grain-scale response in ferroic polycrystals under electric field

Abstract: Understanding coupling of ferroic properties over grain boundaries and within clusters of grains in polycrystalline materials is hindered due to a lack of direct experimental methods to probe the behaviour of individual grains in the bulk of a material. Here, a variant of three-dimensional X-ray diffraction (3D-XRD) is used to resolve the non-180° ferroelectric domain switching strain components of 191 grains from the bulk of a polycrystalline electro-ceramic that has undergone an electric-field-induced phase … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
20
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

5
4

Authors

Journals

citations
Cited by 30 publications
(22 citation statements)
references
References 36 publications
1
20
1
Order By: Relevance
“…(b) was calculated for an average over a group of grains of similar orientation at a variety of group sizes. It was found that the RMS distance was halved for groups of 10 similarly oriented grains as compared to individual grains, which agrees well with our previous measurements of grain‐scale heterogeneity . The present work builds on this by combining the domain volume‐fraction information with the 3D microstructure grain map, reconstructed from the near‐field data and shown in Fig.…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…(b) was calculated for an average over a group of grains of similar orientation at a variety of group sizes. It was found that the RMS distance was halved for groups of 10 similarly oriented grains as compared to individual grains, which agrees well with our previous measurements of grain‐scale heterogeneity . The present work builds on this by combining the domain volume‐fraction information with the 3D microstructure grain map, reconstructed from the near‐field data and shown in Fig.…”
Section: Resultssupporting
confidence: 90%
“…It was found that the RMS distance was halved for groups of 10 similarly oriented grains as compared to individual grains, which agrees well with our previous measurements of grain-scale heterogeneity. 47 The present work builds on this by combining the domain volume-fraction information with the 3D microstructure grain map, reconstructed from the near-field data and shown in Figure 4 where individual grains are colored by the non-180°d omain switching strains at (a) e p,F0 and (b) e p,F2 , extracted from far-field data. The combination of these two results enables a correlative study of ferroelastic strain response with microstructural features of the grains themselves as well as their local neighborhoods.…”
Section: Strain Response Heterogeneitymentioning
confidence: 99%
“…For example, powder diffraction measurements of BaTiO3 typically identify the average crystal symmetry at room temperature as tetragonal, not triclinic [31]. However, grain-scale mechanical interactions may locally break the crystal symmetry inferred from the powder-averaged aggregate [32]. Figures 2 and 3 show the topological origin of this anomaly; strain gradients in many directions that, when averaged over many grains within the aggregate, result in isotropic peak broadening and diffuse scattering that obscures the true local symmetry.…”
Section: Correlating Strain Symmetry and Functional Responsementioning
confidence: 99%
“…11,14 The magnitude of this compliance or intergranular coupling effect, as well as its influence on the macroscopic strain properties, is not thoroughly understood. It has also been demonstrated that the magnitude of the electric-field-induced strain response in phase change piezoelectric ceramics is highly heterogeneous at the grain scale, 15 adding further evidence to the importance of understanding the coupling of properties between grains. These local compliance effects are expected to vary the response of the polycrystalline microstructure under different constraint conditions.…”
mentioning
confidence: 99%